PTU-084 Barrett's oesophagus: a qualitative study of patient burden and follow up needs. (8th June 2018) - Britton, James; Hamdy, Shaheen; Mclaughlin, John; Horne, Maria; Ang, Yeng
Abstract : Introduction: The rising incidence of Barrett's oesophagus (BO) has implications on both service provision and patient burden. Few studies have assessed the impact on patients or engaged them in the design of care pathways. This qualitative study aims to: 1) identify factors impacting on BO patients' health-related quality of life; 2) explore their follow up needs and attitudes to new models of follow up care. Methods: An exploratory qualitative approach was utilised using 20 semi-structured, in-depth one-to-one interviews, audio recorded and transcribed verbatim. Patients undergoing BO surveillance at a single district general hospital were recruited using purposive sampling with the aim of achieving maximum variation in terms of age, sex and disease duration. Interviews focused on the impact of surveillance, physical and psychological symptoms, experiences of follow-up care, follow-up needs and new models of follow-up care. New models of care included a dedicated BO service and patient-initiated consultation by means of telephone or virtual clinic. Data were analysed using Framework approach, supported by NVivo Pro 11. Results: Data saturation occurred after 20 participant interviews. Median age was 63 years (range 42–77 years) and median disease duration was 5.6 years (range 1–15 years). 10 subthemes and three main themes emerged from data analysis: 1) Burden of disease – symptom control, worry of oesophageal cancer and surveillance endoscopy; 2) Follow up experiences – historic and current follow up care, at this DGH, was found to be inconsistent and often inadequate to meet patients' needs and expectations. In particular, a lack of disease specific information; 3) Follow up needs – participants sought enhanced communication, organisation and structure of care. They valued face to face interaction with a specialist and were more likely to follow their advice. The concept of direct secondary care access in-between endoscopies was reassuring to participants. There was a strong preference towards a telephone patient-initiated consultation over an 'impersonal' online system. Conclusions: This qualitative research provides an in-depth account of the patients' perspective of BO in an NHS setting. The potential burden to patients must be considered when implementing future care pathways or when designing a BO specific patient reported outcome measure. To improve patient experiences we recommend the implementation and prospective assessment of a complex care intervention, which encompasses dedicated BO surveillance, outpatient clinic and telephone direct access line.